PENGARUH PERENCANAAN PAJAK, INTENSITAS MODAL DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN - Nur’anah, Nur’anah; Khodijah, Ina; Komarudin, Mochamad Fahru (Yayasan Education and Social Center, 2025)
The healthcare sector is one of Indonesia's strategic sectors, playing a crucial role in national development, with rapid growth especially during and after the COVID-19 pandemic. However, the financial performance of companies in the Healthcare Equipment & Providers sub-sector has fluctuated due to both external and internal challenges, such as capital management and leverage. This study aims to analyze the effect of tax planning, capital intensity, and leverage on the financial performance of companies in this sub-sector listed on the Indonesia Stock Exchange for the period 2020-2024. The research adopts a quantitative method using secondary data from the financial statements of 7 companies over five years, analyzed with multiple linear regression. The results show that tax planning has a significant positive effect on financial performance, capital intensity has no significant effect, and leverage has a significant negative effect on financial performance. The study concludes that effective tax planning strategies and optimal leverage management are essential for improving company financial performance, while capital intensity needs to be managed efficiently but does not directly affect financial performance.